Peran Guru Pendidikan Agama Kristen Dalam Meningkatkan Prestasi Belajar Siswa Sekolah Menengah Kejuruan Bhakti Insani Kota Bogor - Hitus, Yosina; Nakmofa, Sutidjo Justus Jerzak (STIPAK Malang, 2025)
Abstract: Christian Religious Education teachers are responsible for fostering intellectual development to enhance students' academic achievement. The decline in students' academic performance is caused by several factors, including a lack of understanding of the teacher's explanations, monotonous and less creative teaching methods, low learning motivation, excessive time spent playing games, and minimal parental or family attention. This study aims to examine the role of Christian Religious Education teachers in improving students' academic performance at SMK Bhakti Insani in Bogor City. The research method used is qualitative, employing a literature study approach, observation, and interviews. To achieve academic success, students require guidance, motivation, creative teaching methods, and attention from Christian Religious Education teachers. Therefore, collaboration between teachers, schools, and parents is essential in helping students enhance their academic performance.Keywords: Role of Teachers; Christian Religious Education; Learning AchievementAbstrak: Guru Pendidikan Agama Kristen memiliki tanggung jawab dalam mencerdaskan dan membangkitkan capaian belajar peserta didik menjadi lebih baik. Menurunnya prestasi belajar siswa disebabkan karena siswa kurang mengerti penjelasan guru, pendekatan dalam belajar yang monoton dan kurang kreatif, motivasi belajar yang rendah, lebih menghabiskan waktu bermain game, dan minimnya perhatian orang tua atau keluarga. Penelitian ini dilakukan guna mengetahui peran guru khususnya guru Pendidikan Agama Kristen, dalam meningkatkan prestasi belajar siswa SMK Bhakti Insani Kota Bogor. Dengan menggunakan metode penelitian kualitatif dengan pendekatan studi pustaka, observasi, dan wawancara. Untuk mendapatkan prestasi belajar, siswa perlu mendapatkan arahan, bimbingan, motivasi, metode pembelajaran yang kreatif, dan perhatian dari guru Pendidikan Agama Kristen. Oleh karenaya, kerjasama antara guru, sekolah, dan orang tua menjadi faktor penting dalam meningkatkan prestasi belajar siswa. Kata kunci: Peran Guru; Pendidikan Agama Kristen; Prestasi Belajar